Application of the Informed Consent Principle in Civil Law: A Case Study of Reduction Operations and Internal Fixation - Yudiman, Twody; Prayuti, Yuyut (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
This article describes the application of the principle of informed consent in civil law, focusing on case studies of internal reduction and fixation operations (ORIF). The research method uses a normative legal approach by analyzing related laws and regulations, related court decisions, and relevant legal literature. Interviews with medical legal practitioners and experienced physicians were conducted to gain practical insight into doctor-patient agreements in ORIF actions. The importance of a holistic and adaptive approach in implementing the principle of informed consent in Indonesia not only covers legal aspects, but also considers cultural, social, and economic factors. This requires active involvement from all relevant parties, as well as increased awareness of patient rights and physician responsibilities. By understanding these challenges, we can improve informed consent systems in the context of ORIF, create a more transparent healthcare environment, and safeguard the principles of patient well-being in medical practice. The results of this study are expected to contribute to a further understanding of the complexities of civil law in the context of informed consent, strengthen ethical principles in medical practice, and provide guidance for stakeholders, including physicians and medical law practitioners with a focus on ORIF actions.